2016
DOI: 10.15407/ujpe61.10.0893
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Interaction Potential between Water Molecules

Abstract: The structure and the explicit form of the interaction potential between molecules in water vapor have been studied. The main contribution to this potential is supposed to be made by repulsive, dispersion, and electrostatic forces. The irreducible contribution caused by the overlapping of the electron shells of water molecules, which is usually associated with hydrogen bonds, is supposed to be small and neglected. Interaction potentials, in which the molecular repulsion is described by either a "soft" power-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
9
0
4
Order By: Relevance
“…Rigorously speaking, these potentials are only correct for a vapor phase, where the screening effect can be ignored. In order to build them we have used an approach similar to that for the water potential [15]. It is shown that the averaged potential can be approximated by the expression, whose structure is close to the one for the Lennard-Jones potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rigorously speaking, these potentials are only correct for a vapor phase, where the screening effect can be ignored. In order to build them we have used an approach similar to that for the water potential [15]. It is shown that the averaged potential can be approximated by the expression, whose structure is close to the one for the Lennard-Jones potential.…”
Section: Resultsmentioning
confidence: 99%
“…H-bonds are considered as a sum of electrostatic interaction and an irreducible one caused by exchange effects arising due to the overlapping of the electronic shells of molecules. It was shown in many works [10][11][12][13][14][15] that H-bond in water is mainly of electrostatic nature. The irreducible part of H-bond, caused by the overlapping of electron shells and corresponding exchange effects, does not exceed 10−15% [14].…”
Section: Bare Potential Of the Interparticle Interaction In Methanolmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Зазначимо, що ефекти екранування враховую-ться тiльки для мультипольних потенцiалiв (МП) [29]. Параметри потенцiалу Ленард-Джонса, що вiдповiдають диполь-дипольнiй взаємодiї двох ди-мерiв, визначенi в Додатку.…”
Section: вплив взаємодIй мономер-димер та димер-димер на температурнуunclassified
“…Звернемо увагу на те, що числовi значення˜( a) m ( ) i m ( ) для SPC-потенцiалу, що розраховуються у [22,29,31], залежать вiд температури (див. рис.…”
Section: внесокunclassified